2005
DOI: 10.1007/s10545-005-0073-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of D‐arabitol and ribitol on neuronal network activity

Abstract: To date, two new defects in the pentose phosphate pathway have been identified in patients with abnormalities in their polyol profiles. Some of them presented with neurological symptoms of so far unknown aetiology. The pathophysiological role of polyols, e.g. in the brain, is relatively unknown. We tested the neurotoxicity of polyols using a 'neurochip' model. After exposure of cortical rat neurons to D-arabitol and ribitol in increasing concentrations up to 10 mmol/L, the electrophysiological activity was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…In agreement with our findings, Klusmann et al (2005) evaluated the neurotoxicity of d ‐arabitol and ribitol, using a neurochip model representing cortical neurons of rats. The exposure of up to 10 mM of polyols did not alter the spontaneous network activity of neurons, indicating the absence or only a secondary effect of polyols on brain dysfunction.…”
Section: Discussionsupporting
confidence: 80%
“…In agreement with our findings, Klusmann et al (2005) evaluated the neurotoxicity of d ‐arabitol and ribitol, using a neurochip model representing cortical neurons of rats. The exposure of up to 10 mM of polyols did not alter the spontaneous network activity of neurons, indicating the absence or only a secondary effect of polyols on brain dysfunction.…”
Section: Discussionsupporting
confidence: 80%
“…Pathological accumulation of polyols might play a role in secondary neuronal damage associated with metabolic diseases, 68,69 even though a direct neurotoxic effect could not be demonstrated. 70…”
Section: Metabolic Correlates Of Neuronal Injury As Biomarkers and Clues To Understanding The Neurodegenerative Processmentioning
confidence: 99%
“…Christensson et al [25] reported the diagnosis of D-arabinitol/L-arabinitol ratios in urine in neutropenic children with cancer for the invasive candidiasis. In addition, Klusmann et al [26] reported that highly elevated concentrations of the C5 polyols, such as arabitol, were found in body fluids in the disorder of ribose-5-phosphate isomerase deficiency. In our study, arabitol was found to be increased in the serum of ovarian cancer patients and the ovarian benign tumor patients, compared to the healthy controls.…”
Section: Discussionmentioning
confidence: 99%